ANALISIS PENGARUH KUALITAS LAYANAN JASA PENDIDIKAN TERHADAP KEPUASAN MAHASISWA PADA KAMPUS STIPER SANTO THOMAS AQUINAS JAYAPURA - Resubun, Ratna Luciana (DINAMIS, 2021)
This study aims to determine and analyze the effect of service quality which consists of variables of physical evidence, reliability, responsiveness, assurance, and empathy partially and simultaneously and dominantly affect student satisfaction at the STIPER Santo Thomas Aquinas Jayapura campus. The sample in this study were students of STIPER Santo Thomas Aquinas Jayapura class of 2017, totaling 100 people. Types and sources of data used are primary and secondary data, primary data can be done by distributing questionnaires directly to students who are on campus. Secondary data in this study were obtained from data on the STIPER Santo Thomas Aquinas Jayapura campus and through documents, reports, internet, and other scientific writings. The analytical method used is the method of multiple linear regression (multi linear regression), while the hypothesis test uses t test and f test with a significant level of 5%. The results showed that the partial test (t), physical evidence, reliability, responsiveness, assurance, and empathy had a significant effect on student satisfaction. Based on the simultaneous test (F), all variables of physical evidence, reliability, responsiveness, assurance and empathy together have a significant effect on student satisfaction. The most dominant factor influencing student satisfaction is guarantee. : , , , , .